See-through, light-through, and color modules for large-area tandem amorphous/microcrystalline silicon thin-film solar modules: Technology development and practical considerations for building-integrated photovoltaic applications. (January 2020) - Tsai, Chin-Yi; Tsai, Chin-Yao
Abstract: See-through, light-through, and color modules are developed for large-area (1.3 m × 1.1 m) tandem amorphous/microcrystalline silicon thin-film solar modules for building-integrated photovoltaic (BIPV) applications. Key technologies for achieving these BIPV functionalities are developed and introduced into the 60 MW production line. These key technologies include post-scribing passivation of nano-size thin-films, large-area film uniformity, front reflective layers, 4-step laser scribing, transverse laser scribing, and peripheral pen-type junction boxes. This paper demonstrates and discusses the potential and versatility of these silicon thin-film modules in BIPV applications. It also shows that the BIPV modules' specifications and performance mainly depend on the key technologies and their associated manufacturing processes in the production line. The electrical and optical performances of the BIPV modules are presented and important issues about their use in BIPV applications are also discussed. Highlights: See-through, light-through, and color a-Si/μ-Si BIPV modules are developed. Key technologies are developed and introduced into the 60 MW production line. Post-scribing passivation, large-area film uniformity, front reflective layers. 4-step laser scribing, transverse laser scribing, peripheral pen-type junction boxes.